Perancangan Mesin Pengering Kopi Otomatis dengan Arduino Uno - Deni Hidayat; Siti Nur Istiqomah (Proklamasi 45 University, 2025)
Processing of agricultural products, especially coffee, has an important role in the economy of rural communities. One of the main stages in coffee processing is the drying process, which aims to reduce the water content to an optimal level in order to maintain the quality of the coffee beans. In Mekar Buana Village, Tegalwaru District, Karawang, the drying process is still done manually, so it takes a long time and produces non-uniform quality. To overcome this problem, this research designed an automatic coffee drying machine based on Arduino Uno with the support of Internet of Things (IoT) technology. This machine allows automatic temperature and humidity settings and can be monitored remotely. Design analysis and static load stress testing were carried out using SolidWorks software to ensure the resistance of the machine structure to operational loads. The research results show that the designed machine is able to work optimally, increase the efficiency of drying time, and maintain the quality of coffee beans better than traditional methods. It is hoped that the implementation of this machine can increase the productivity of coffee farmers and support technological innovation in the agricultural sector.